Dynamic Three-Dimensional ADC Changes of Parotid Glands During Radiotherapy Predict the Salivary Secretary Function in Patients With Head and Neck Squamous Carcinoma - Feng, Mei; Yin, Qingping; Ren, Jing; Wu, Fei; Lan, Mei; Wang, He; Wang, Min; Li, Lu; Chen, Xiaojian; Lang, Jinyi (Frontiers in Oncology, 2021)
Objective: To investigate the changes of three-dimensional apparent diffusion coefficient (3D-ADC) of bilateral parotid glands during radiotherapy for head and neck squamous carcinoma (HNSCC) patients and explore the correlations with the radiation dose, volume reduction of parotid gland and the salivary secretary function. Materials and Methods: 60 HNSCC were retrospectively collected in Sichuan cancer hospital. The patients were all received diffusion-weighted imaging (DWI) scan at pre-radiation, the 15th radiation, the 25th radiation and completion of radiation Dynamic 3D-ADC were measured in different lobes of parotid glands (P1: deep lobe of ipsilateral; P2: superficial lobe of ipsilateral; P3: deep lobe of contralateral; P4: superficial lobe of contralateral), and the 3D-ADC of spinal cord were also recorded. Chewing stimulates test, radionuclide scan and RTOG criteria were recorded to evaluate the salivary secretary function. Pearson analysis were used to assess the correlation between 3D-ADC value, radiation dose, volume change, and salivary secretary function. Results: The mean 3D-ADC of parotid glands increased. It had begun to change at the 15th radiation and the mostly increased in P1. However, there was no changes for the maximum and minimum 3D-ADC. The 3D-ADC of spinal cord changes were almost invisible (ratio≤0.03±0.01). The mean 3D-ADC was negatively correlated with the salivary secretary function (r=-0.72) and volume reduction of different lobes of parotid glands (r1=-0.64; r2=-0.61; r3=-0.57; r4=-0.49), but it was positively correlated with the delivered dose (r1=0.73; r2=0.69; r3=0.65; r4=0.78). Conclusion: Dynamic 3D-ADC changes might be a new and early indicator to predict and evaluate the secretary function of parotid glands during radiotherapy.